Harold C. Fleming papers - Fleming, Harold C.; Gibson, James O.; Levin, Arthur J.
Correspondence, memoranda, speeches, writings, annual reports, subject files, proposals, background material, news releases, pamphlets and booklets, biographical material, and other papers pertaining primarily to Fleming's work as executive vice president and president of the Potomac Institute, Washington, D.C. The collection documents the efforts of the institute to eliminate racial discrimination, expand African American civil rights, and foster cooperation among private and public agencies to achieve these goals through the institute's sponsorship of research programs, publications, and conferences. Also includes papers of James O. Gibson and Arthur J. Levin, other executives with the institute.
Topics include Harry S. Ashmore, Hazel Brannon Smith, affirmative action in the armed forces, compliance with the Civil Rights Act of 1964 by state and local governments and police, equal opportunity in employment and housing, fairness in mortgage policies and zoning, improvement of inner city economic development and schools, national youth service, occupational training, the poor and children of the poor, race relations, and school integregation.
Organizations represented include American Civil Liberties Union, American Friends Service Committee, American Institute of Architects, Anti-Defamation League of B'nai B'rith, Black Arts Council (Washington, D.C.), Center for the Study of Democratic Institutions, Congressional Black Caucus, D.C. Black Repertory Company, International City Management Association, Leadership Conference on Civil Rights, NAACP Legal Defense and Educational Fund, National Association for the Advancement of Colored People, National Association of Intergroup Relations Officials, National Committee Against Discrimination in Housing, National Conference of Christians and Jews, National Urban Coalition, New World Foundation, Southern Christian Leadership Conference, Southern Regional Council, United States-South Africa Leader Exchange Program, White House Conference on Balanced National Growth and Economic Development, and the White House Conference : "To Fulfill These Rights."
Correspondents include Will D. Campbell, Audrey Currier, Stephen R. Currier, G.W. Foster, Lloyd K. Garrison, John Hope, Vernon E. Jordan, Burke Marshall, George McMillan, Paul Moore, Benjamin Muse, John Silard, and John G. Simon.
Civil rights leader and executive with the Potomac Institute, Washington, D.C. Full name: Harold Curtis Fleming. Born 1922; died 1992.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Ashmore, Harry S; Campbell, Will D. -- Correspondence; Currier, Audrey -- Correspondence; Currier, Stephen R. -- Correspondence; Foster, G. W. -- 1919- -- Correspondence; Garrison, Lloyd K. -- 1897- -- Correspondence; Hope, John, -- 1909- -- Correspondence; Jordan, Vernon E. -- 1935- -- Correspondence; Marshall, Burke, -- 1922-2003 -- Correspondence; McMillan, George -- Correspondence; Moore, Paul, -- 1919- -- Correspondence; Muse, Benjamin -- Correspondence; Silard, John -- Correspondence; Simon, John G. -- 1928- -- Correspondence; Smith, Hazel Brannon; American Civil Liberties Union; American Friends Service Committee; American Institute of Architects; Black Arts Council (Washington, D.C.); B'nai B'rith. -- Anti-defamation League; Center for the Study of Democratic Institutions; Congressional Black Caucus; D.C. Black Repertory Company; International City Management Association; Leadership Conference on Civil Rights; NAACP Legal Defense and Educational Fund; National Association for the Advancement of Colored People; National Association of Intergroup Relations Officials; National Committee Against Discrimination in Housing; National Conference of Christians and Jews; National Urban Coalition (U.S.); New World Foundation; Potomac Institute (Washington, D.C.); Southern Christian Leadership Conference; Southern Regional Council; United States; United States-South Africa Leader Exchange Program; Affirmative action programs; African Americans -- Civil rights; African Americans in the performing arts -- Washington (D.C.); Civil rights -- United States; Discrimination in employment -- United States; Discrimination in housing -- United States; Discrimination in mortgage loans -- United States; Economic assistance, Domestic -- United States; Exchange of persons programs, American; Exchange of persons programs, South African; Inner cities -- United States; Occupational training -- United States; Police -- United States; Poor -- United States; Poor children -- United States; Race discrimination -- United States; Urban schools -- United States; Youth -- Services for -- United States; Zoning, Exclusionary -- United States; United States -- Armed Forces -- Minorities; United States -- Race relations; Civil rights leaders